Energy projection analysis of solar energy for water pump system using gridline power with focus on control system - Chan, Christoper Sing Kong (2013)
Experiment is undertaken to determine the possibilities of creating a solar powered pump system to reduce the power wastage in an Evacuated Tube Solar Collector water circulation system at Pekan campus (3˚ 30’ N, 103˚ 25’ E) Faculty of Mechanical Engineering, University Malaysia Pahang. The experiment kicks off by creating a test rig to hold the solar panel in place and creating a cut-in cut-out (CiCo) system to help reduce the pump energy consumption. CiCo system is developed to cut-in and cut-out the pump based on the temperature difference between the Evacuator outlet and the storage tank. Malaysia lies in the equatorial zone with an average daily solar insolation of more than 900 W/m2 and can reach a maximum of 1200 W/m2 for most of the year. Due to different weather pattern which will block and reduce the solar isolation, CiCo system can help reduce the power consumption of the pump when the temperature has reach the threshold set in the codding set in PIC18F4550 detected by two thermostat LM35DZ. G.T. Power RC Wattmeter is connected to a solar panel to determine the total energy output of the panel. A multifunctional mini ammeter is connected to the pump to measure the energy consumption of the pump with or without connecting the CiCo system. Based on the experiment the maximum panel required to create a solar powered pump system without using the CiCo system is 18 panels. However when connected to CiCo system the number of panel required is decreased to five panels. This show the minimum required panel if UMP decided to create a solar powered pump system in the campus.